Learning experience on career planning for community colleges in Malaysia - Ahmad Rosli Mohd Nor; Mohamad Sattar Rasul; Salleh Amat; Jasmi Abu Talib; Nurul Atiqah Ab Raji; Md Mosharaf Hossain (International Journal of Evaluation and Research in Education (IJERE), 2023)
This study explored a learning experience in technical and vocational curriculum based on a career planning program. The aspect of career has always been ignored in the community college curriculum as it was considered less important in the education of students. Many studies showed that exposure to career since the early days of schooling are very effective in shaping the career maturity of students. This study has been conducted based on Backward Design curriculum model which used learning outcomes (graduation) as a tool to create a learning experience in the curriculum. This qualitative study was conducted on 15 respondents graduated from community college and are successful in their careers with a high income. Data was collected using Delphi techniques interview and each session had been transcribed. Thematic analysis has been conducted in 1st round Delphi techniques interview and Fuzzy Delphi Method (FDM) analysis has been used in second round of the Delphi Techniques. Findings indicate that there are three items learning experiences for pre-self-employment information (interests, self-efficacy, and intrinsic motivation) and four items of learning experiences for pre-employment career that influence the career planning. The item has been ranking base on priority for each items value of threshold (d) in FDM. Finally, in the conclusions and recommendations sectors the data identified by the research are described in detail and analyzed so that to ensure that the chain relationship of market research > curriculum design > vocational education and training will be effective and successful.